Cutaneous cryptococcosis - Quartarolo, Nicole (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
Cutaneous cryptococcosis, caused by the encapsulated yeast, Cryptococcus neoformans, is generally associated with concomitant systemic infection. The authors report a case of a man with isolated cutaneous cryptococcosis of his right foot without obvious systemic manifestations. A review of the clinical aspects, pathogenesis and management of cutaneous cryptococcosis is also presented.
Keywords: Cryptococcosis; Cryptococcus Neoformans; Foot Dermatoses; Isolation And Purification; Kriptokokoza; Middle Age; Srednja leta; Stopalo, dermatoze